Having more siblings delays menarche in Indonesia. Issue 6 (17th October 2018) - Kim, Dohyung; Sohn, Kitae
Abstract: Objectives: Tanner (1968, Scientific American, 218(1), 21–27) concluded that having more siblings delayed menarche, but many subsequent studies have reported diverging results. We thus aimed to investigate whether the initial conclusion remains valid by controlling for sibship size and birth order together, analyzing a large number of observations, drawing on a nationally representative sample, adjusting for childhood socioeconomic status, and considering a developing country. We additionally aimed to assess the importance of sibling sex for age at menarche. Methods: We analyzed 10 212 ever‐married women aged 20+ in the last wave of the Indonesian Family Life Survey. We regressed age at menarche on sibship size, birth spacing, and childhood socioeconomic status. We subsequently divided sibship size into the numbers of brothers and sisters. Results: Having more siblings was related to later menarche, and the relationship was strengthened when the birth order was controlled for. In addition, those born earlier experienced menarche later. Sibling sex was irrelevant to age at menarche, boosting the importance of sibship size itself. Conclusions: Our results support the earlier conclusion that having more siblings delays menarche.